Deep amplicon sequencing screening benzimidazole resistance associated specific single nucleotide polymorphisms in isotype-1 β-tubulin from trichostrongyloids on ruminant farms in northeast Germany - Marc Borchert; Jürgen Krücken; Stefan Fiedler; Paula Ehnert; Wiebke Weiher; Ricarda Daher; Stephan Steuber; Georg von Samson-Himmelstjerna (Veterinary Parasitology, 2026)

Knockdown resistance in Stomoxys calcitrans stable fly populations on German dairy farms: kdr alleles explain susceptibility of individual flies to deltamethrin - Ricarda Daher; Jürgen Krücken; Burkhard Bauer; Virginia Maria Góes da Silva; Sophia Reissert; Wiebke Weiher; Ard M. Nijhof; Peter-Henning Clausen; Stephan Steuber (Journal of Pest Science, 2025)
The stable fly, Stomoxys calcitrans, is a globally important pest causing stress, economic losses and transmission of pathogens in livestock. Control on commercial farms relies predominantly on the use of insecticides, with pyrethroids being the most frequently used class of insecticides in industrialised countries. Here, laboratory isolates were obtained from four dairy farms in Brandenburg (Germany) and tested for phenotypic resistance to deltamethrin in comparison to a susceptible reference isolate using topical application. Individual flies were subsequently genotyped using allele-specific real-time PCRs. Phenotypic resistance was observed in all four field isolates with resistance ratios between 46 and 119 compared to the susceptible laboratory strain. At position 1014 of the voltage-sensitive sodium channel, allele-specific PCRs detected the wild-type , kdr-his and kdr genotypes encoding leucine, histidine and phenylalanine, respectively. In the susceptible laboratory isolate, only the wild-type was identified. On the farms with very high LD 50 values, the kdr variant was most prevalent and logistic regression analysis revealed that the kdr variant increased the odds to survive exposure to deltamethrin more than the kdr-his genotype. Flies carrying two resistance alleles were less susceptible than flies that also carried one wild-type allele. In three out of four field isolates, the allele frequencies were significantly different from the expectations of the Hardy–Weinberg equilibrium suggesting ongoing selection. The data show that the phenotype can be largely explained by the kdr genotype and represent high frequencies of the L1014F kdr and L1014H kdr-his variants conferring high levels of resistance in northern Germany.

Coproscopical diagnosis of patent Fasciola hepatica infections in sheep – A comparison between standard sedimentation, FLUKEFINDER® and a combination of both - Alexandra Kahl; Georg von Samson-Himmelstjerna; Christina S. Helm; Jane Hodgkinson; Diana Williams; Wiebke Weiher; Werner Terhalle; Stephan Steuber; Jürgen Krücken (Veterinary Parasitology, 2023)